2023
DOI: 10.1111/pai.14002
|View full text |Cite
|
Sign up to set email alerts
|

Drug provocation tests in children: All that glitters is not gold

Luis Moral,
Francesca Mori

Abstract: A proper allergy work‐up, based on the gold standard drug provocation test (DPT), usually rules out suspected drug hypersensitivity in children. These tests are generally open, given their high efficiency compared with double‐blind placebo‐controlled DPTs. Although their negative predictive value is excellent, no studies have calculated their positive predictive value, highly dependent on the prevalence of the disease. Most studies have found a rate of <5%–10% of true beta‐lactam hypersensitivity in childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…This finding calls into question the results of many of the tests that presented mild manifestations but were not verified with a new DPT, as well as the results of the published studies that do not specify how many of the reactions observed in the DPT were doubtful and how many DPTs were repeated. 62 Another limitation is the relevant proportion of patients (5.8%) who did not complete the study and in whom the result could not be verified, most of them due to refusal or loss to follow-up.…”
Section: Re Sultsmentioning
confidence: 99%
“…This finding calls into question the results of many of the tests that presented mild manifestations but were not verified with a new DPT, as well as the results of the published studies that do not specify how many of the reactions observed in the DPT were doubtful and how many DPTs were repeated. 62 Another limitation is the relevant proportion of patients (5.8%) who did not complete the study and in whom the result could not be verified, most of them due to refusal or loss to follow-up.…”
Section: Re Sultsmentioning
confidence: 99%
“…DPT continues to be widely regarded as the gold standard for confirming or excluding drug allergies (126). Although there is no consensus regarding DPT protocols, there is evidence on the safety and efficacy of DPT in children depending on risk stratification (42,57,76,111,(127)(128)(129)(130)(131)(132)(133).…”
Section: How To Optimize Dpt In Children?mentioning
confidence: 99%